Pesantren Peace Theology as a Framework of Islamic Public Ethics: Negotiating the Religion-Politics Nexus in Contemporary Indonesia - Abd Munib; Khairuddin; Erfan Efendi; Dahlan Nur Busri; Moh. Asy’ari (Islamika Inside: Jurnal Keislaman dan Humaniora, 2026)
The growing politicization of religion in contemporary Indonesia has increasingly transformed religious values into instruments of political contestation, thereby weakening the ethical function of religion, intensifying democratic polarization, and undermining social cohesion. While previous studies have examined pesantren as Islamic educational institutions, civil society actors, or promoters of religious moderation, the conceptual foundations of pesantren as a framework of Islamic Public Ethics remain theoretically underdeveloped. This study synthesizes scholarship on pesantren, Islamic political thought, and public religion to construct Pesantren Peace Theology as a framework of Islamic Public Ethics for negotiating the religion–politics nexus in contemporary Indonesia. Employing a qualitative conceptual research design, documentary sources were analyzed through document analysis and synthesized using Jaakkola's theory synthesis approach involving concept identification, conceptual integration, and theoretical proposition development. The study constructs Pesantren Peace Theology as an integrated framework comprising four ethical dimensions—Ethical Political Engagement, Moral Autonomy, Intergroup Mediation, and Non-Partisan Social Engagement—which collectively constitute an ethical mechanism through which pesantren negotiate the religion–politics nexus by preserving moral autonomy, fostering public trust, facilitating inclusive dialogue, and promoting the common good. The study contributes to scholarship on public religion and Islamic political thought by constructing Pesantren Peace Theology as a framework of Islamic Public Ethics that explains how religious institutions can participate in democratic politics without becoming instruments of partisan political contestation, thereby providing a conceptual foundation for strengthening democratic coexistence in Indonesia's plural public sphere.